If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2v + 3) = 28 Reorder the terms: -4(3 + 2v) = 28 (3 * -4 + 2v * -4) = 28 (-12 + -8v) = 28 Solving -12 + -8v = 28 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -8v = 28 + 12 Combine like terms: -12 + 12 = 0 0 + -8v = 28 + 12 -8v = 28 + 12 Combine like terms: 28 + 12 = 40 -8v = 40 Divide each side by '-8'. v = -5 Simplifying v = -5
| g(5)=6x+7 | | .55*5= | | y-7=6/7(x-6) | | 7lnx-3(lnx^3+5lnx)=0 | | 1.2y+3=.36x | | -51-9x=-2x+95 | | x+7=2(x) | | y-3=4(x+5) | | 3x+11+5x-9=360 | | 2-18/x^2 | | 80+11x-10=360 | | 2x+(-5)=3x+(-1) | | y-7=-5(x+8) | | secx-tanx=cscx-1/cotx | | 2m-0.5=1.7 | | 12y-30=18 | | -4(w+7)=24 | | 8=2x/0.200-x | | y+6=-7(x+5) | | (18-8x)/4x | | -11=x-5-1 | | 2y+4x-3w=19 | | -4x+68=0 | | 15-1(5m-4)=34 | | (x+3)(x+4)(2)=0 | | 3/4×2×12=j | | -38-12x=-8x+18 | | 5x^2-18x+8=0 | | .25=s-5 | | 5x^2-18x+9x=0 | | -7/5b=21 | | 7-7/5b=21 |